PENGARUH MODEL PEMBELAJARAN LANGSUNG BERBASIS PRAKTIKUM TERHADAP KETERAMPILAN PROSES SAINS DAN KEMAMPUAN BERPIKIR KRITIS SISWA - Syintia Lestari; Saidil Mursali; Ida Royani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2018)
This study aims to determine the effect of practicum based direct learning models on science process skills and students' critical thinking skills. This type of research is a quasi-experimental design with Pretest-posttest Control Group Design. Sampling technique using Cluster Random Sampling. The sample in this study were students of class XI IPA 4 as the experimental class and XI IPA 3 as the control class. The research instrument used in the form of learning implementation observation sheets, observation sheets of science process skills and tests of students' critical thinking skills. The data obtained were analyzed using t-test. The results of the data analysis show that the implementation of learning in both classes reaches very good categories. Data analysis of students 'science process skills shows that students' science process skills differ. Students' critical thinking ability in the experimental class using practicum based direct learning models is higher than the control class. The average students' critical thinking skills in the experimental class reached 73.5 and control class 58.6. Hypothesis test analysis using t-test is known that tcount is greater than ttable (3.45 > 2.04), therefore the hypothesis is accepted. Based on the results of these studies it can be concluded that the practicumbased direct learning model influences students 'critical thinking skills and students' average process science skills reach good categories.